(untitled) (Journal of Educational Sciences, 2021)
The article presents an analysis of the terms of systems thinking, revealing the methodology of the concepts of "thinking", "activity", "thinking" and "theory of activity", "scientific thinking", "structure of activity", "form of activity", "educational activity", "labor activity ”,“ research activity ”. The objectives and methods of research have been clarified. The review of psychological, pedagogical, philosophical literature is carried out. The ideas and statements about the thinking of the great second teacher of the world Abu Nasyr Al Farabi are analyzed. The provisions on the theory of thinking and activity in the works of famous Russian psychologists A.N. Leontiev, S.L. Rubinstein, B.G. Ananyev. The research is based on the directions of the developed methodology of the mental activity of the famous scientist G.P. Shchedrovitsky, who defined the pragmatic approach of scientific and systems thinking. The meaning of the concept "system" is revealed, where the learned critical thinking by students is studied, ensuring the development of their creative, research activities. Summing up the results of mental activity in the system of scientific and methodological research, as an important tool, we schematically show the logic of the formation of educational, labor, research activities of students. One of the important and significant indicators of our research was the description of the content and learning outcomes in the study of a compulsory discipline, contributing to the formation of ideas about the methodology of the science of students’ mental activity. To implement the main goal of teaching the discipline "Philosophy and Methodology of Pedagogy", the structure of the textbook is outlined, the expected results and the achievement of certain indicators by teachers are disclosed. Key words: activity, thinking, theory of activity, systems thinking, human psyche, educational activity, labor activity, research activity, cognitive activity, semantic structure, personal tasks, systemic research, methodological thinking, innovative potential.